Single-ion chelation strategy for synthesis of monodisperse Pd nanoparticles anchored in MOF-808 for highly efficient hydrogenation and cascade reactions. Issue 30 (21st July 2022) - Zhao, Ke; Zhang, Le-Xi; Xu, Heng; Liu, Yi-Fei; Tang, Bo; Bie, Li-Jian
Abstract : A single-ion chelation strategy was proposed to in-situ construction of a Pd-nano@MOF-808-Pza catalyst with high activity for various hydrogenation and cascade reactions (Pd-nano = Pd nanoparticle, Pza = 2, 3-pyrazinedicarboxylic acid). Abstract : Ultrafine Pd nanoparticles are prepared using a single-ion precursor on a MOF-808 carrier. The ligand 2, 3-pyrazinedicarboxylic acid (Pza) is dispersed in porous MOF-808 via grafting on formic acid sites, and thus Pd 2+ ions are chelated by Pza to form a new single-ion precursor Pd@MOF-808-Pza. Then a Pd-nano@MOF-808-Pza catalyst is prepared by direct reduction of this precursor using NaBH4 . Material characterization reveals the homogeneous dispersion of 3–6 nm Pd nanoparticles within the MOF-808 matrix. Pd-nano@MOF-808-Pza exhibits excellent catalytic activity in the hydrogenation of unsaturated nitrogen-containing compounds, and other typical reactions, such as the Knoevenagel condensation, Suzuki/Heck cross-coupling, and hydrogen tandem reactions. In addition, density functional theory (DFT) calculations are carried out to elucidate the chelation of Pd 2+ ions by Pza on MOF-808 and propose mechanisms of hydrogenation reactions. This work provides an effective reduction catalyst, and more importantly, a single-ion chelation strategy for design and synthesis of metal supported catalysts.